Sultantepe. Anglo-Turkish Joint Excavations 1952 - Lloyd, Seton
Progress of the Excavations — The Assyrian Acropolis — Assyrian Pottery — Assyrian Objects from Room M. 2 (Ivories, Bead Object, Pictorial Encrustation — Vessels of Faience and Glass, Vessels of Faience and Stone).